Analisis Perbedaan Antara Pembiayaan Bank Syariah Dengan Kredit Bank Konvensional : Analisis Variabel Utama Pembiayaan - Ina Andriyani; M. Fuad Hadziq; Rini Febrianti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This paper discusses the differences between Islamic bank financing and conventional bank credit. This research method is descriptive qualitative by analyzing the basic theory of the fundamental differences between Islamic bank financing and credit at conventional banks. The data was collected using literature studies from scientific journals and basic sharia economics books. Meanwhile, data analysis uses tabulation, coding, editing and verification or conclusion methods. Conventional banks prioritize and prioritize the complete guarantee aspect, whereas in sharia banks it only focuses on the character aspect of the customer itself, meaning that it can be said that the sharia bank believes that the customer will have good intentions when providing credit or financing within a certain agreed period of time.